The Moral Foundations of Populist Communication: A Semantic Network Analysis of Political Parties’ Social Media Discourse in a Multiparty System - Anna Wickenkamp; Frederic R. Hopp; Michael Hameleers; Linda Bos (Social Media + Society)
Social media have transformed political campaigning by enabling direct interaction between politicians and voters, becoming a key tool for shaping public opinion. Moral language is pivotal in this dynamic as it captures attention in an overly information-saturated social media environment and wields significant influence over political opinions. Populists thrive on social media by fostering distrust in elites, using emotional language, and reducing complex issues to simple “us vs. them” binaries. We argue these factors are rooted in moral underpinnings, which may play a significant role in the appeal of populist parties and have thus far received limited scholarly attention. Consequently, this paper addresses the research question: To what extent, and in what ways, do populist parties exhibit a distinct moral-rhetorical profile on social media that sets them apart from mainstream politicians? Using Moral Foundations Theory, natural language processing, and a computational semantic network approach, we analyzed 11,205 social media posts from Dutch political parties and leaders during the 2023 Dutch election campaign across X, Facebook, and Instagram. Our findings reveal that populist parties emphasize Care and Authority over other moral foundations, while mainstream parties exhibit a different moral foundation distribution. These results align with the part of populist communication logic that frames populist actors as defenders against corrupt elites and external threats, as well as representatives of the people’s demand for sovereignty. Moreover, we found populist parties exhibit less internal consistency in their moral rhetoric across platforms than mainstream parties, suggesting a potentially higher adeptness at tailoring messages to different platforms and their affordances.